European perspectives on environmental law and governance - Kingston, Suzanne, 1977- (Routledge research in EU law, 2013)
"This book provides a range of perspectives on some of the most pressing contemporary challenges in EU environmental law and governance from some of today's leading European environmental academics and practitioners. The book maintains a focus on three key cross-cutting issues, each of which is carefully analysed through the lens of governance. The first theme to be addressed is that of climate change and the problems it poses for EU governance. The second issue explored concerns the challenge of integrating environmental considerations into other policy areas, as is required by the Treaty on the Functioning of the European Union and the EU's Charter of Fundamental Rights. Finally, the third theme centres on the important challenge of improving environmental enforcement within the EU, and considers issues such as the Aarhus Convention and the evolution of the Commission's work on implementation and enforcement throughout the past twenty years. Each of these three themes is situated within the broader ongoing debate about the changing nature of European environmental governance post-Lisbon and the ways in which developments in this area fits within broader trends in European governance theory and policy generally. European Perspectives on Environmental Law and Governance contains contributions from experts in the field including; Mary Robinson, Alan Boyle, Ludwig Kramer and Liam Cashman, and will be of interest to academics, students and practitioners of EU environmental law"--